Linking Local and Global Sustainability - Sandhu, Sukhbir.; Sandhu, Sukhbir.; McKenzie, Stephen.; McKenzie, Stephen.; Harris, Howard.; Harris, Howard. (The International Society of Business, Economics, and Ethics Book Series, 2014)
The book takes a holistic approach to sustainability. Acknowledging the Brundtland definition, that sustainable development meets the needs of the present without compromising the ability of future generations to meet their own needs, the book is specifically concerned with the ethics of contemporary social and environmental sustainability activity and thinking. It is concerned with the role of institutions–both local and global in achieving sustainability initiatives. All twelve chapters extend sustainability–conceptually, empirically and theoretically, and in doing so provide insights into linking local and global sustainability. The book refocuses sustainability as a series of interwoven and dynamic relationships, backed by just ethical decision-making, which begin locally, and reach out to impact the global level.